Aerobic exercise improves quality of life, psychological well-being and systemic inflammation in subjects with Alzheimer's disease - El-Kader, Shehab M. Abd; Al-Jiffri, Osama H (African health sciences, 2016)
Background: Alzheimer's disease has a destructive drawbacks on the patient and his/her entire family as this disease badly affects the behavior, cognition and abilities to do activities of daily living (ADL). The physical and mental benefits of exercise are widely known but seldom available to persons suffering from Alzheimer's disease. Objective: The aim of this study was to measure quality of life, systemic inflammation and psychological well-being response to aerobic exercises in Alzheimer's. Methods: Forty Alzheimer elderly subjects were enrolled in two groups; the first group received treadmill aerobic exercise, while the second group was considered as a control group and received no training intervention for two months. Assessment of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), Rosenberg Self-Esteem Scale (RSES),Beck Depression Inventory (BDI), Profile of Mood States(POMS) and SF-36 health quality of life (SF-36 HRQL) were taken before and at the end of the study. Results: There was a 25.2%, 19.4%, 23.5%, 21.3%, 17.7% , 11.7%, 12.5% and 10.1 % reduction in mean values of TNF-α, IL-6, BDI, POMS, health transition SF-36 subscale, bodily pain SF-36 subscale, role functioning: emotional SF-36 subscale and mental health SF-36 subscale respectively in addition to 15.7%, 13.1%, 12.6%, 11.1%, 13.2% and 11.2 % increase in mean values of RSES, physical functioning SF-36 subscale, role functioning:physical SF-36 subscale, general health SF-36 subscale, Vitality SF-36 subscale and Social functioning SF-36 subscale respectively in group (A) received aerobic exercise training, so that there was a significant reduction in the mean values of TNF-α, IL-6, BDI & POMS and increase in the mean values of SF-36 HRQL subscale scores, RSES in group (A) as a result of aerobic exercise training, while the results of group (B) who received no training intervention were not significant. Also, there were significant differences between mean levels of the investigated parameters in group (A) and group (B) at the end of the study (P<0.05). Conclusion: Treadmill walking exercise training is an effective treatment policy to improve quality of life, systemic inflammation and psychological wellbeing in Alzheimer's.